The Transmutation of Deference in Medicine: An Ethico-Legal Perspective. (12th April 2018) - Devaney, Sarah; Holm, Søren
ABSTRACT: This article critically considers the question of whether an increase in legal recognition of patient autonomy culminating in the decision of the Supreme Court in Montgomery v Lanarkshire Health Board in 2015 has led to the death of deference to doctors, not only within the courts and healthcare regulatory arenas in England and Wales but also in the consulting room and the health care system more broadly. We argue that deference has not been eradicated, but that the types of deference paid to doctors and to the medical profession have changed. In addition, whilst traditionally deference was extended towards the medical profession, increasing instances of deference being shown to other parties in the healthcare setting can be identified, allowing wider debate or recognition of the complexity of understandings, interests and aims of all those involved. Finally, we note instances in which deference to the medical profession has become more hidden.